![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^5+x+1=x^5-x^2+x^2+x+1=x^2\left(x^3-1\right)+\left(x^2+x+1\right)=x^2\left(x-1\right)\left(x^2+x+1\right)+\left(x^2+x+1\right)\)
\(=\left(x^2+x+1\right)\left(x^3-x^2+1\right)\)
\(x^{10}+x^5+1=x^{10}-x+x^5-x^2+x^2+x+1=x\left(x^9-1\right)+x^2\left(x^3-1\right)+\left(x^2+x+1\right)\)
\(=x\left(x^3-1\right)\left(x^6+x^3+1\right)+x^2\left(x-1\right)\left(x^2+x+1\right)+\left(x^2+x+1\right)\)
\(=x\left(x-1\right)\left(x^2+x+1\right)\left(x^6+x^3+1\right)+x^2\left(x-1\right)\left(x^2+x+1\right)+\left(x^2+x+1\right)\)
\(=\left(x^2+x+1\right)\left[x\left(x-1\right)\left(x^6+x^3+1\right)+x^2+1\right]\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=\left(x^2+3x+1\right)\left(x^2+3x-3\right)-5\)
Đặt \(t=x^2+3x+1\) thì A thành
\(t\left(t-4\right)-5=t^2-4t-5\)
\(t^2-5t+t-5=t\left(t-5\right)+\left(t-5\right)\)
\(=\left(t-5\right)\left(t+1\right)=\left(x^2+3x+1-5\right)\left(x^2+3x+1+1\right)\)
\(=\left(x^2+3x-4\right)\left(x^2+3x+2\right)\)
\(=\left(x-1\right)\left(x+1\right)\left(x+2\right)\left(x+4\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
x^5+x^4+1=x^5+x^4+x^3-x^3-x^2-x+x^2+x+1=x^3(x^2+x+1)-x(x^2+x+1)+x^2+x+1=(x^3-x+1)(x^2+x+1)
\(x^5+x^4+1\)
\(=x^3\left(x^2+x+1\right)-x\left(x^2+x+1\right)+\left(x^2+x+1\right)\)
\(=\left(x^3-x+1\right)\left(x^2+x+1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có : x5 - x4 + x4 - x3 - x4 + x3 - x2 + x2 - x + x - 1
= x4(x - 1) + x3(x - 1) - x3(x - 1) - x2(x - 1) + x2(x - 1) + (x - 1)
= (x4 + x3 - x3 - x2 + x2 + 1) (x - 1)
= (x4 + 1)(x - 1)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có:
\(x^5+x^4+1\)
\(=x^5+x^4+x^3+1-x^3\)
\(=\left(x^5+x^4+x^3\right)+\left(1^3-x^3\right)\)
\(=x^3\left(x^2+x+1\right)+\left(1-x\right)\left(1+x+x^2\right)\)
\(=\left(x^2+x+1\right)\left(x^3+1-x\right)\)
\(a^5+a^4+1=a^5+a^4+a^3-a^3+a^2-a^2+a-a+1\)
\(=a^5+a^4+a^3-a^3-a^2-a+a^2+a+1\)
\(=\left(a^5+a^4+a^3\right)-\left(a^3+a^2+a\right)-\left(a^2+a+1\right)\)
\(=a^3\left(a^2+a+1\right)-a\left(a^2+a+1\right)+\left(a^2+a+1\right)\)
\(=\left(a^2+a+1\right)\left(a^3-a+1\right)\)
#by_Suho
\(x^2-5\)
\(=\left(x-\sqrt{5}\right)\left(x+\sqrt{5}\right)\)
\(x^2^{ }-5=x^2-\sqrt{5}=\left(x-5\right)\left(x+5\right)\)